Hybridising metaheuristics and exact methods for portfolio optimisation problem - Cui, Tianxiang (2016)
This thesis focuses on the portfolio optimisation problems, which concern with allocating the limited capital to invest in a number of potential assets (investments) in order to achieve the investors risk appetites and the return objectives. In the 1950s, Harry Markowitz proposed a mean-variance portfolio optimisation model, which is widely regarded as the foundation of the modern portfolio theory. However, the basic Markowitz mean-variance model has limited practical utilities since it omits many constraints existed in real world trading. The problem quickly becomes more complex with the additional real-world trading constraints involved.